Baḥtsul Masāil at a Traditional Islamic Educational Institution in Aceh: Teungku Dayah's Contribution to the Development of Islamic Law - Zulkhairi, Teuku; Hajar, Ibnu; Safriadi, Safriadi; Marzuki, Marzuki; Saifullah, Saifullah (Islamic Family Law Department, Sharia and Law Faculty, Universitas Islam Negeri Ar-Raniry, 2024)
The global world has implications for the emergence of various contemporary problems and demands legal certainty for every Islamic legal issue. This research aims to examine Baḥtsul Masāil in Dayah as a traditional Islamic educational institution in Aceh, especially its contribution in responding to developments in contemporary Islamic law. This research uses a qualitative-normative method with a sociological approach to Islamic law. Data was obtained through interviews, observation and document study. The informants interviewed were Tengku Dayah in Aceh, observing the activities of Baḥtsul Masāil and the documents studied were journal articles, textbooks and books. The research results show that teungku dayah is able to answer contemporary Islamic law problems through Baḥtsul Masāil. This activity took the form of a focus group discussion involving professional staff from Islamic boarding schools and discussed various current issues from a legal perspective. In Baḥtsul Masāil uses the method of ilhaq and contextualization of the turats text. Ilhaq is achieved by equating law with problems that have not been answered by Islamic texts with problems that have been answered by Islamic texts, while contextualization of Islamic texts is achieved by interpreting Islamic texts in a contemporary context. The results of Baḥtsul Masāil are then disseminated to the community through community learning processes, recitations, or religious lectures. Thus, in terms of the sociology of Islamic law, Teungku Dayah and Dayah educational institutions as actors are able to contribute to contemporary Islamic problems and the problem of the vacuum of Islamic law in society can be overcome.